Students’ Perception toward the Implementation of Blended Learning in Essay Writing Class of the Third Semester Students English Department Universitas Negeri Padang - Lia Utami; M. Zaim (Journal of English Language Teaching, 2022)
Blended learning as one of the suggested learning methods to be implemented during pandemic covid-19 era is more effective and efficient learning for current situaton and it increase the attractiveness of learning. However, blended learning also has its downside, such as media required is very diverse so there are some difficulties in applying it when the infrastructure does not support. This advantages and disadvantages resulted in essay writing class’ students having different perceptions on the blended learning. The purpose of this study is to find out students’ perceptions toward implementing Blended Learning method at English Department, Universitas Negeri Padang as well as its benefit for the students. This research used descriptive method. The sample for this research was 83 third semester essay writing class’ students of English Department in Universitas Negeri Padang. The data collection technique used in this research was a questionnaire with 6 indicators through google form application. Therefore, the results of this study showed that the majority of essay writing class’ students in English Department had a good perception of the implementation of blended learning in essay writing class. The students agree that the use of blended learning improves students’ ability in evaluating, analyzing and synthesizing their essay that leads to a better achievement in essay writing class and also make it efficient both in time and financial. However, the students still encounter an obstacles such as shifting from online to offline to online class and accessing virtual classes.